Sustainable Landscape Study of Sindang Barang Cultural Village, Bogor Regency - Wakyudi, Wakyudi; Hanum, Nia Namirah; Kenzo, Himalaya Bima (RUSTIC, 2026)
Sindang Barang Cultural Village is a local cultural settlement located in Tamansari District, Bogor Regency, covering an area of approximately 8,600 square meters. The village comprises 29 traditional Sundanese buildings and is characterized by a harmonious atmosphere and a community that strongly upholds inherited cultural traditions. Beyond its function as a cultural tourism destination, Sindang Barang serves as a living settlement where daily activities are closely intertwined with the preservation of Sundanese values passed down through generations. Its existence is crucial in the context of cultural conservation, as it provides a tangible example of the coexistence of traditional architecture, cultural practices, and environmental harmony. This study aims to examine the ecosystem conditions of Sindang Barang Cultural Village within the context of community life. A descriptive research method was employed, utilizing direct observation and literature review through general observations of the settlement. The findings indicate that Sindang Barang Cultural Village exhibits a distinct Sundanese residential landscape character, physically expressed through the form, layout, and continuity of traditional Sundanese architecture.